Introducing a multiscalar framework for biocluster research: A meta-analysis - David Ayrapetyan; Frans Hermans (Sustainability, 2020)
Bioclusters have grown in popularity in the last decade in response to the global environmental and climate challenges. These clusters envisage sustainable and local production value chains in different sectors of the bioeconomy. However, the sustainability of these clusters is often questioned because of the negative social and environmental effects they can have both inside and outside of their region. At present, a framework is missing to analyze these effects that span multiple levels and multiple scales. The aim of this paper is to develop such a multiscalar framework. For this aim, we conducted a meta-analysis of biocluster case studies. As a result, we constructed a framework that combines the aspects of sustainability, knowledge and resource flows, cluster network properties, and the political and institutional structures. We tested this framework on the question of how the different scales of biocluster performance interact and depend on each other.
Keywords: 330; bioeconomy; biocluster; sustainability; scales; transition; meta-analysis